Affirmations of God and man : writings for modern dialogue - Fuller, Edmund, 1914-2001. (New York : Association Press, 1967)
A collection of brief statements, largely from contemporary writers such as Buber, Hammarskjold, Tillich, Chesterton, Donne and Heschel on the idea of God, man and creation.
The idea of God --
The idea of man --
The secular challenge --
Religion and science --
Creation and existence --
Faith.
Bibliography: p. 153-156.
Keywords: Christian literature